SINERGITAS STAKEHOLDERS DALAM IMPLEMENTASI KEBIJAKAN EKOLOGI PENGELOLAAN SAMPAH TERPADU: (Studi pada Dinas Lingkungan Hidup Kabupaten Kediri) - Novita Sari, Leni (Jurnal Administrasi Publik, 2023)
Synergity Analysis Of Stakeholders In The Implementation Of Integrated Waste Management Ecological Policy (Study At Kediri District Environmental Services). This research aims to determine the synergy of stakeholders in waste management in Kediri Regency. This research method uses a qualitative descriptive approach. The results of this research show that in solving the problem recommended by researchers, namely creating a cadre of waste management in each sub-district and conducting evaluations every 2 weeks, as well as the role of the government, namely that the government has not been able to attract investors into waste management in Kediri Regency. And the communication network that exists in synergy between stakeholders in waste management in Kediri Regency is still lacking, where socialization is only carried out to villages or sub-districts that are ready to build 3R TPS and socialization has not been carried out to all villages in Kediri Regency regarding waste management.